Developing Assessment Instruments for Procedural Writing of Managing Flight Emergency and Urgency Situations: Examining Indonesian Aviation English Instructors’ Perceptions - Raga Pratama; Nur Mukminatien; Fatmawati Fatmawati; Suhono Suhono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Despite the critical need for written communication and emergency management proficiency in aviation, existing research in aviation English education has primarily emphasized speaking and listening skills, neglecting cadets’ writing abilities. This gap is particularly concerning given the International Civil Aviation Organization (ICAO) Annex 10 requirements, which demand accurate and coherent documentation in emergency scenarios. Addressing this void, the present study aimed to develop reliable and valid assessment instruments for assessing aviation cadets’ procedural writing skills in managing flight emergency and urgency situations. This study also examined the Indonesian Aviation English instructors’ perceptions on the developed assessment instruments. Employing a Research and Development (R&D) design using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—the study constructed test instructions and an analytic scoring rubric based on learning indicators derived from ICAO Annex 10. The instruments underwent expert validation (CVI = 1.00) and were trialed with 24 third-semester aeronautical communication cadets. The inter-rater reliability test showed good consistency (ICC = 0.802–0.890), confirming the rubric’s reliability in practical use. Results revealed that the instruments effectively assessed both linguistic skills and operational understanding. Aviation English instructors found the assessment instruments pedagogically valuable as they promoted integrated language learning and critical thinking skills through the application of a sequenced procedure in managing flight emergency and urgency situations. However, limitations include the small sample size and the absence of multimodal performance assessments. Future research should expand implementation across diverse aviation academies and explore integration with AI-driven tools or scenario-based simulations. This study contributes to English for Specific Purposes (ESP) pedagogy by providing a validated framework for enhancing and assessing domain-specific writing in high-stakes professional contexts.